Effect of winemaking techniques on polysaccharide composition of Cabernet Sauvignon, Syrah and Monastrell red wines. (10th October 2013) - Apolinar‐Valiente, R.; Romero‐Cascales, I.; Williams, P.; Gómez‐Plaza, E.; López‐Roca, J.M.; Ros‐García, J.M.; Doco, T.
Abstract Background and Aims Several authors have demonstrated the interesting properties of wine polysaccharides. These compounds act as protective colloids and are able to interact with tannins and anthocyanins in wines, reducing their reactivity and increasing colour stability. Little, however, is known about the release of polysaccharides by winemaking technologies. We examine the effect of several winemaking techniques – cold prefermentative maceration, dry ice addition and grape skin freezing, and addition of two maceration enzymes – on the quantity and composition of polysaccharides extracted from the three red wine cultivars – Cabernet Sauvignon, Syrah and Monastrell. Methods and Results The molecular mass distribution and composition of polysaccharides were determined, respectively, by high‐performance size‐exclusion chromatography and by gas chromatography. The amount of some polysaccharide fractions extracted depended on the grape cultivar. The addition of commercial pectic enzyme preparations released a greater quantity of polysaccharides in all three cultivars studied and altered the polysaccharide composition of the Cabernet Sauvignon wine. The effect of the other treatments on the amount of polysaccharides depended on the cultivar. Conclusion This study confirms that grape cultivar and winemaking technique have a significant impact on the quantity and composition of polysaccharides extracted from grapes into wine. The concentration of polysaccharides rich in arabinose and galactose, and in rhamnogalacturonan II was greater in the Syrah wine than that in the Cabernet Sauvignon and Monastrell wines. Both enzymatic treatments and also dry ice addition had a significant influence on the polysaccharide concentration and composition of the wines made from a given cultivar, whereas cold prefermentative maceration or grape skin freezing had no effect. Significance of the Study This is the first report that shows that the polysaccharide composition of Cabernet Sauvignon, Syrah and Monastrell wines is affected by winemaking technique.